Antithymocyte globulin/antilymphocyte globulin plus kidney-nourishing Chinese Medicinal： effect on severe aplastic anemia - Tang, Xudong; Liu, Feng; Li, Liu; Liu, Chi; Zhang, Shanshan; Xiao, Haiyan; Zheng, Chunmei; Xu, Shu; Ma, Rou (Journal of traditional Chinese medicine, 2012)
OBJECTIVE： To explore the effect of antithymocyte globulin （ATG）/antilymphocyte globulin （ALG） plus kidney-nourishing Chinese medicinal （KNCM） on se- vere aplastic anemia （SAA）. METHODS： Twenty-five subjects of severe aplastic anemia were treated with ATG/ALD plus KNCM be- tween 1992 and 2009, and the clinical data before and after treatment were collected and analyzed. RESULTS： Of the 25 patients, 9 were nearly cured, 6 were improved, 5 were in remission, and 5 failed. The overall effective rate was 80.0%. The 3-year, 5-year, 10-year, 15-year survival rate were respec- tively 98.6%, 97.3%, 97.3%, 67.5%, and median sur- vival time was 180 months. Compared to the condi- tions before administering the medication of ATG/ ALG plus KNCM, after 2 weeks, reticulocyte was first improved （P=0.001）, one month later, followed by palette （P=0.037）, two months later, by neutrophil cell in peripheral blood （P=0.001）; three months lat- er, then by the hemoglobin （P=0.012）. By conduct- ing 1-year follow-up, 1 case of complication--parox-ysmal nocturnal hemoglobinuria （PNH） was identi- fied and the patient still alive today. CONCLUSION： ATG/ALG fect on SAA and could rate. plus KNCM had better ef- improve patients＇ survival